The Role of the Central and Kuibyshev Institutes of Maternal and Child Welfare in the Creation of Maternal and Child Health Care Service in the USSR (1922–1940) - R. S. Serebryany; S. A. Sher; O. V. Yaremchuk (Вопросы современной педиатрии)
The article focuses on the role of the State Research Institute of Maternal and Child Welfare as the lead establishment and of the Kuibyshev Regional Scientific-Practical Institute of Maternal and Child Welfare in the creation of maternal and child health care service in the Soviet Union during 1922–1940. It also presents the scientific-practical, educational, organizational-methodological activities of the central and peripheral institutions, their comparative characteristics and contribution to the creation of a broad network of institutions for maternal and child welfare (nurseries, maternity welfare centres, baby food centers, social-legal offices) and the reduction of morbidity and mortality of infants and young children.